PERENCANAAN INSTALASI PENGOLAHAN AIR BERSIH (IPA) UNIT BEKOTOK KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - FITRIYADI, NUR (KURVA S JURNAL MAHASISWA, 2014)
Water Treatment Plant (IPA) PDAM Unit Bekotok Tenggarong District, Kutai regency is processing package system with discharge capacity of 20 liters / sec. The processing of the water is raw water from a tributary of the Mahakam river known bekotok and has served several villages and villages among which village maluhu, mangkuraja, jahab and jonggon village with house connections (SR) of 1966 as regulars.Relative to population growth as well as social infrastructure that exists today, the Water Treatment Plant (IPA) PDAM Unit Bekotok Tenggarong District is not able to serve the water needs of society and social infrastructure, so that distribution is currently done pengiliran.So to be able to serve the needs of clean water mentioned above in order to maintain necessary measures and efficient strategic and planning for the needs of 10 (ten) years into the future, so that the needs of the community and the public as well as the smooth development can be met and there is no rotation